2017
DOI: 10.21206/rbas.v7i1.372
|View full text |Cite
|
Sign up to set email alerts
|

Propagação De Gabirobeiras via Estaquia Associada Ao Ácido Indolbutírico

Abstract: RESUMO -Uma das ameaças ao cerrado é a exploração de certas espécies nativas, que tem sido feita de forma extrativista e muitas vezes predatória, tornando-se imprescindíveis ações no sentido de se fazer o cultivo e domesticação destas espécies. Dentre as inúmeras frutíferas nativas que possuem alto potencial para exploração comercial, destaca-se a gabirobeira, que se encontra sob forte pressão devido ao impacto causado pela fragmentação das suas populações, seja pelo extrativismo inadequado, ou pela expansão d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
0
7
1
Order By: Relevance
“…However, contrary results were reported during the autumn season by Pereira et al (2017), when cuttings were supplemented at a maximum IBA concentration of 3200 mg L -1 , and it was obtained a 80.71% survival for C. adamantium and a 100% survival for C. pubescens. These results showed that for the same species, discordant responses can occur due to concentrations and biological material, making it important to define the ideal concentration, and the most favorable time for species propagation, validating the importance of studys related to propagation vegetative by cuttings.…”
Section: Resultscontrasting
confidence: 62%
See 2 more Smart Citations
“…However, contrary results were reported during the autumn season by Pereira et al (2017), when cuttings were supplemented at a maximum IBA concentration of 3200 mg L -1 , and it was obtained a 80.71% survival for C. adamantium and a 100% survival for C. pubescens. These results showed that for the same species, discordant responses can occur due to concentrations and biological material, making it important to define the ideal concentration, and the most favorable time for species propagation, validating the importance of studys related to propagation vegetative by cuttings.…”
Section: Resultscontrasting
confidence: 62%
“…Pereira et al (2017) did not observe calogenesis in the cuttings of C. adamantium and C. pubescens demonstrating the variability for the same species. According to the observed data, callus formation in both species demonstrated tissue competence for the dedifferentiation process, although insufficient for root induction.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…According to Hartmann et al (2011), among these hormones, auxins have a direct effect on roots formation in vegetative propagation, as they favor cellular activity and also act in signaling molecules in the development of events for root formation. They are considered the most important substances that promote adventitious rooting, mainly for species that have difficulty in rooting (PEREIRA et al, 2017), with the indole-3-butyric acid (IBA) being the most used auxin to stimulate the rooting of propagules, due to its low toxicity for most species (TRONCO et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Its exploitation is extractive, performed in an inadequate way (Pereira et al 2017). Its use by the industry is incipient (Freitas et al, 2008), but its fruits can be used for consumption in natura, production of sweets (jellies, pans, puddings, sorbets), juices, liqueurs and wine (Pavan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%